Dosimetric effect of intrafraction motion and different localization strategies in prostate SBRT. (July 2020) - Vanhanen, A.; Poulsen, P.; Kapanen, M.
Highlights: CBCT-guided pre-treatment localization strategy may lead to inaccurate treatment delivery. Additional pre-treatment position correction increases the accuracy of treatment delivery. Continuous motion monitoring ensures correct target coverage and minimizes OAR doses for every fraction. Abstract: The aim of this study was to evaluate the dosimetric effect of continuous motion monitoring based localization (Calypso, Varian Medical Systems), gating and intrafraction motion correction in prostate SBRT. Delivered doses were modelled by reconstructing motion inclusive dose distributions for different localization strategies. Actually delivered dose (strategy A) utilized initial Calypso localization, CBCT and additional pre-treatment motion correction by kV-imaging and Calypso, and gating during the irradiation. The effect of gating was investigated by simulating non-gated treatments (strategy B). Additionally, non-gated and single image-guided (CBCT) localization was simulated (strategy C). A total of 308 fractions from 22 patients were reconstructed. The dosimetric effect was evaluated by comparing motion inclusive target and risk organ dose-volume parameters to planned values. Motion induced dose deficits were seen mainly in PTV and CTV to PTV margin regions, whereas CTV dose deficits were small in all strategies: mean ± SD difference in CTVD99% was –0.3 ± 0.4%, −0.4 ± 0.6% and –0.7 ± 1.2% in strategies A, B and C, respectively. Largest dose deficits were seen in individual fractions for strategy C (maximum dose reductions were −29.0% and –7.1% for PTVD95% and CTVD99%, respectively). The benefit of gating was minor, if additional motion correction was applied immediately prior to irradiation. Continuous motion monitoring based localization and motion correction ensured the target coverage and minimized the OAR exposure for every fraction and is recommended to use in prostate SBRT. The study is part of clinical trial NCT02319239.